Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection: Triggering a Lethal Fight to Keep Control of the Ten-Eleven Translocase (TET)-Associated DNA Demethylation? - Kouidou, Sofia (Pathogens, 2020)
The extended and diverse interference of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in multiple host functions and the diverse associated symptoms implicate its involvement in fundamental cellular regulatory processes. The activity of ten-eleven translocase 2 (TET2) responsible for selective DNA demethylation, has been recently identified as a regulator of endogenous virus inactivation and viral invasion, possibly by proteasomal deregulation of the TET2/TET3 activities. In a recent report, we presented a detailed list of factors that can be affected by TET activity, including recognition of zinc finger protein binding sites and bimodal promoters, by enhancing the flexibility of adjacent sequences. In this review, we summarize the TET-associated processes and factors that could account for SARS-CoV-2 diverse symptoms. Moreover, we provide a correlation for the observed virus-induced symptoms that have been previously associated with TET activities by in vitro and in vitro studies. These include early hypoxia, neuronal regulation, smell and taste development, liver, intestinal, and cardiomyocyte differentiation. Finally, we propose that the high mortality of SARS-CoV-2 among adult patients, the different clinical symptoms of adults compared to children, the higher risk of patients with metabolic deregulation, and the low mortality rates among women can all be accounted for by the complex balance of the three enzymes with TET activity, which is developmentally regulated. This activity is age-dependent, related to telomere homeostasis and integrity, and associated with X chromosome inactivation via (de)regulation of the responsible XIST gene expression.